KARAKTERISTIK KEKUATAN CAMPURAN HRS-WC AKIBAT PERUBAHAN SUSUNAN SARINGAN - ., Sapuan; Erwan, Komala; Sulandari, Eti (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2016)
This study aims to determine how much influence the proportion of aggregate mixture due to missing one or two sieve fractions of mixture Hrs-wc and measure how much force the mixture against the road pavement structure with the characteristic parameter Marshall due to missing one or two sieve fractions. For the results of the experiments that have been done show that the normal use of the filter, without filter and without filter 3/8 8 shows the results were quite varied although the total amount of aggregate use roughly the same at 41.5%, for the normal filter produces the best KAO with 7 , 07%, the highest stability values ​​(1305 Kg), Flow (4.20 mm), VIM (4.75%), VFB (81.5%) and MQ (310.7 kg / mm). The results of the overall marshall test obtained for unscreened 3/8 and 8 available KAO value (7.07%) and (7.25%) with a value of stability (in 1160 and 1050 Kg), a value flow (4.08 mm and 3.90 mm), the value MQ (284.3 Kg / mm and 269.2 kg / mm), the value of the VFB (81.0% and 79.5%), the value of VIM (4.90% and 5.50 %). The results of the three variations indicate that the change in the composition sieve fraction does not significantly affect the strength characteristics of asphalt mix everything still meet the standards of the general specifications of the public works agency Directorate General of Highways. Keywords: Filter, Aggregate Composition Coarse, Marshall Test